Dosage-dependent tumor suppression by histone deacetylases 1 and 2 through regulation of c-Myc collaborating genes and p53 function - Heideman, Marinus R; Wilting, Roel H; Yanover, Eva; Velds, Arno; de Jong, Johann; Kerkhoven, Ron M; Jacobs, Heinz; Wessels, Lodewyk F; Dannenberg, Jan-Hermen (Blood, 2013)
Histone deacetylases (HDACs) are epigenetic erasers of lysine-acetyl marks. Inhibition of HDACs using small molecule inhibitors (HDACi) is a potential strategy in the treatment of various diseases and is approved for treating hematological malignancies. Harnessing the therapeutic potential of HDACi requires knowledge of HDAC-function in vivo. Here, we generated a thymocyte-specific gradient of HDAC-activity using compound conditional knockout mice for Hdac1 and Hdac2. Unexpectedly, gradual loss of HDAC-activity engendered a dosage-dependent accumulation of immature thymocytes and correlated with the incidence and latency of monoclonal lymphoblastic thymic lymphomas. Strikingly, complete ablation of Hdac1 and Hdac2 abrogated lymphomagenesis due to a block in early thymic development. Genomic, biochemical and functional analyses of pre-leukemic thymocytes and tumors revealed a critical role for Hdac1/Hdac2-governed HDAC-activity in regulating a p53-dependent barrier to constrain Myc-overexpressing thymocytes from progressing into lymphomas by regulating Myc-collaborating genes. One Myc-collaborating and p53-suppressing gene, Jdp2, was derepressed in an Hdac1/2-dependent manner and critical for the survival of Jdp2-overexpressing lymphoma cells. Although reduced HDAC-activity facilitates oncogenic transformation in normal cells, resulting tumor cells remain highly dependent on HDAC-activity, indicating that a critical level of Hdac1 and Hdac2 governed HDAC-activity is required for tumor maintenance.